The contribution of the US monetary policy in the Caribbean business cycles - Borda, Patrice ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 1999)
Uses 12 Caribbean countries as case studies to specify and estimate a panel vector auto regressive model for GDP, real exchange rate, consumer price index and world interest rate.